Gut microbiota-regulated unconjugated bilirubin metabolism drives renal calcium oxalate crystal deposition - Shujue Li; Wenzheng Wu; Yuhao Zhou; Shike Zhang; Daqiang Wei; Mingzhao Zhu; Xiaoling Ying; Xinyuan Sun; Hongxing Liu; Wei Zhu; Daolin Tang; Renjie Jiao; et al. (Gut Microbes)
Gut microbial dysbiosis and the resultant metabolic disorder are intimately associated with calcium oxalate (CaOx) stone formation. Renal CaOx crystal deposition is one of the primary initiating factors of CaOx formation; however, the critical signaling metabolites communicating along the gut–kidney axis, and their regulation on renal CaOx crystal deposition remain unclear. Here, we investigate the role of gut microbiota-associated unconjugated bilirubin (UCB) metabolism in renal CaOx crystalline pathogenesis. The UCB was first distinguished as a significant risk factor of renal CaOx crystal deposition, by transplantation of fecal microbiota derived from healthy rat (healthy-FMT) to alleviate the renal CaOx crystal deposition in rat models, which was also testified in CaOx stone patients. Further experiments showed that UCB could increase renal CaOx crystal deposition significantly in both rat and Drosophila models. Mechanistically, UCB can promote apoptosis in renal tubular epithelial cells, enhance oxalate secretion by upregulating Slc26a6 expression, and facilitate CaOx crystal nucleation and aggregation, all of which contribute to renal CaOx crystalline pathogenesis. Furthermore, we identified significant gut microbiota dysbiosis in renal CaOx crystal deposition rats, particularly in β-glucuronidase (β-GD) and bilirubin reductase (BilR)-related dysbiosis, which modulate UCB levels and its enterohepatic circulation. These findings suggest that UCB is a novel regulator of renal CaOx crystal deposition, and targeting its metabolism via modulation of the gut microbiota may offer a promising therapeutic strategy for preventing renal CaOx crystal deposition-related nephropathy.